PREOPERATIVE HALP SCORE AS A PREDICTOR OF SURVIVAL IN LOCALLY ADVANCED COLON CANCER: Colon cancer and HALP score - Amado, Andreia; Pimenta, Joana; Queirós, Tatiana; Leite, Mariana; Tavares, Amélia; Cardoso, João; Gandra, Lurdes; Oliveira, Manuel (JOURNAL OF SURGICAL AND CLINICAL RESEARCH, 2022)
Introduction: Lower preoperative hemoglobin (H), albumin (A), lymphocyte (L) and platelet (P) score (HALP) has been identified as a predictive factor in LACC to categorize patients with higher risk of poor outcome. Therefore, it is important to identify biomarkers available in clinical practice that can predict survival and patient’s prognosis. Our aim is to evaluate preoperative HALP score and its prognostic value. Materials and Methods: Our retrospective study included patients with LACC submitted to oncologic resection between January 2015 to December 2019 in our institution. LACC included stages II and III adenocarcinoma. HALP score was calculated as H (g/L) x A (g/L) x L (/L) / P (/L). A cutoff value was determined by ROC curve analysis and patients were divided accordingly into two groups (low and high HALP) to compare cancer-specific survival, through Kaplan-Meyer curve. Results: In our study, 127 patients were included. The mean age was 70,7 ± 11,9 years and 67 (52,8%) were male. Stage II incorporated 65 patients (51,2%) and stage III 62 (48,8%). The median follow-up time was 37 months. The HALP cutoff value estimated was 22,5. Age ³ 65 years, right-sided tumor, surgical reintervention and cancer-specific survival were associated with a lower HALP scores (p=0,002; p=0,004; p=0,008 and p=0.001, respectively). Conclusion: Nutritional and systemic inflammation status are extremely important in colon cancer prognosis. Serum biomarkers, such as HALP score could easily identify patients with a higher risk of poor outcome. Thus, this prognostic index may be useful as a clinical predictor of survival for LACC patients.